Measles Resurgence in Europe: An Open Breakthrough in the Field of Vaccine-Preventable Diseases - Maria Antonia De Francesco (Pathogens, 2023)
Measles is a highly transmissible respiratory infection due to an enveloped, negative single-stranded RNA virus, belonging to the genus Morbillivirus, the family Paramyxoviridae and the subfamily Orthoparamyxovirinae [...]